The appearance of a single left atrial tachycardia as two different types on preoperative surface and intracardiac ECG of pacemaker due to progressive cardiac conduction disturbance. Issue 8 (15th July 2020) - Sakamoto, Yusuke; Osanai, Hiroyuki; Uno, Hiroto; Kurokawa, Hideki; Kondo, Shun; Tokuda, Kotaro; Kanbara, Takahiro; Nakashima, Yoshihito; Asano, Hiroshi; Ajioka, Masayoshi
Abstract: We treated a patient with PCCD whose single left AT appeared as two different types on preoperative surface and intracardiac ECG from a pacemaker. The diagnosis was hindered by the fact that the conduction block encompassed interatrial block and the pacemaker A‐wave was captured at the right atrial appendage. Abstract : We treated a patient with PCCD whose single left AT appeared as two different types on preoperative surface and intracardiac ECG from a pacemaker. The diagnosis was hindered by the fact that the conduction block encompassed interatrial block and the pacemaker A‐wave was captured at the right atrial appendage.